Hamstring-and-lower-back flexibility in male amateur soccer players - O'Brien, J.; Finch, C. F. (Clinical Journal of Sport Medicine, 2017)
Objective: This study investigated the hamstring-and-lower-back flexibility (HLBF) of male adult amateur soccer players, using the sit-and-reach test (SRT), with a view to obtaining population-based reference values and to determining whether SRT scores are associated with player characteristics. Design: Cross-sectional cohort study. Setting: Teams from high-level Dutch amateur soccer competitions were recruited for participation. Participants: Dutch male high-level amateur field soccer players (n = 449) of age 18 to 40 years. Players with a hamstring injury at the moment of SRT-measurement or any other injury that prevented them from following the SRT protocol were excluded. Main Outcome Measures: Sit-and-reach test scores were measured and then population-based reference values were calculated as follows: >2SD below mean (defining "very low" HLBF), 1SD-2SD below mean ("low" HLBF), 1SD below mean to 1SD above mean ("normal" HLBF), 1SD-2SD above mean ("high" HLBF), and >2SD above mean ("very high" HLBF). Whether SRT scores were correlated with player characteristics was determined using a Pearson correlation coefficient or Spearman rho. Results: Sit-and-reach test scores ranged from 0 to 43.5 cm (mean 22.0 cm, SD 9.2). The cutoff points for population-based reference values were <3.5 cm for "very low", 3.5 to 13.0 cm for "low", 13.0 to 31.0 cm for "normal", 31.0 to 40.5 cm for "high", and >40.5 cm for "very high". Sit-and-reach test scores were significantly associated with players' height (p = 20.132, P = 0.005), body mass index (r = 0.114, P = 0.016), and history of anterior cruciate ligament surgery (P < 0.001). Conclusions: This study is the first to describe the HLBF of amateur soccer players. The SRT reference values with cutoff points may facilitate evidence-based decision making regarding HLBF, and the SRT might be a useful tool to assess injury risk, performance, or for diagnostic purposes. ABSTRACT FROM AUTHOR